Synthesis of New Propargylated 1-Pyrindane Derivatives as Rasagiline Analogues - Pereira, Cidália Silva; Salgado, Sofia; Rizzo-Aguiar, Fabio; Garcia-Mera, Xerardo; Rodríguez-Borges, José E. (Synlett, 2013)
Rasagiline is a compound with important neuroprotective activity applicable to the treatment of neurodegenerative diseases. This work describes an easy and straightforward methodology to the synthesis of new propargylated rasagiline analogues derived from commercially available 6,7-dihydro-5H-cyclopenta[b]pyridine.
Keywords: neuroprotective drugs; pyrindanes; Boekelheide rearrangement; Swern oxidation; reductive amination